Short, medium and long-term results of a series of percutaneous mitral dilatation - Thabet, H.; Gribaa, R.; Slim, M.; Lagren, A.; Hraiech, A.; Ouannes, S.; Neffati, E.; Boughzala, E. (Archives of Cardiovascular Diseases Supplements, 2020)
Rheumatic mitral stenosis (MS) is a common valvulopathy in Tunisia. When tight, percutaneous mitral dilatation (PMD)is the treatment of choice in young subjects with favorable valvular anatomy. Describe clinical and echocardiographic features of patients with tight MS before and after short, medium and long-term of PMD. This is a retrospective, monocentrique, and a descriptive study of patients in our cardiology department between 2012 and 2018 who were hospitalized for PMD with MS. Ninety patients were identified. Age of discovery of MS:35 years(10 to 66),female predominance(68.88%)of which 8 were pregnant. TTE pre-dilatation showed: a mean mitral area (MA) at 1cm2, the Average Transmitral Gradient (ATG) was 11.3mmHg. Bi-commissural fusion in76.7%; Mitral insufficiency(MI) was minimal: 55.6%.75 patients had PAH with an average SPAP at 43.2mmHg. The right cavities (RC) were dilated in 20%. After PMD success in 93.3%. Incidents were worsening of MI in 7 cases, newly created MI in 14 cases, pericardial effusion in 2 patients. TTE immediately after PMD showed: MA at 1.79cm2 (1.2 to 2.4cm2): an improvement of more than 50% in the initial MA. ATG became 5.46mmHg, an average decrease of 4.8mmHg. MI was not created or worsened in 76.6%. Both commissures were completely open in 65.5%. After 6 months of PMD: 60.7% of patients became asymptomatic, 31.1% remained dyspnea. Two patients had ischemic stroke. TTE at 6 months showed MA at 1.7cm2, SPAP decreased in all patients, PAH (which was present before PMD) disappeared in 38.9%.RC are no longer dilated in 14 patients. In the long term 33,3% remained asymptomatic, 54.8% developed dyspnea, 36.7% developed AF. The duration of surveillance was 5.5years on average. Mitral restenosis was observed on 5 years after PMD in 55.7%. The attitude was to make a new PMD in 24.5%and a mitral valve replacement (MVR) for the other patients. PMD has a place in the treatment of MS but it should not be at the expense of MVR which has well its indications.